Corporate Sustainable Performance And Firm Value: A Systematic Review And TCCM-Based Research Agenda - Frandy Walean; Deske W. Mandagi (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
As sustainability becomes increasingly embedded in corporate strategy and investment decision-making, understanding how Corporate Sustainable Performance (CSP) contributes to Firm Value has emerged as a critical research priority. Despite extensive scholarly attention, existing knowledge remains fragmented across theoretical perspectives, methodological approaches, and thematic domains, limiting the development of a coherent understanding of the sustainability–value relationship. This study systematically reviews the CSP–Firm Value literature to synthesize its theoretical foundations, methodological characteristics, and major research themes while identifying future research opportunities through the Theory–Context–Characteristics–Methodology (TCCM) framework. Following the PRISMA guidelines, 558 peer-reviewed journal articles published between 1994 and 2025 were retrieved from the Scopus database and analyzed using systematic review and content analysis procedures. The findings reveal that Stakeholder Theory, the Resource-Based View, and Agency Theory constitute the dominant theoretical lenses used to explain the sustainability–value relationship. Methodologically, the field is largely dominated by quantitative approaches, particularly econometric analysis and Structural Equation Modeling. The review further identifies six major thematic streams: corporate social responsibility and firm performance, sustainable development and environmental management, ESG disclosure and governance, carbon performance and environmental outcomes, stakeholder value creation, and sustainability communication. Based on the TCCM framework, the study highlights important opportunities for future research, including greater theoretical integration, broader contextual coverage, increased attention to mediating and moderating mechanisms, and the adoption of longitudinal and mixed-method approaches. By consolidating fragmented knowledge and providing a structured research agenda, this study offers an integrated understanding of how sustainability contributes to firm value and advances future scholarship in this field.